Effect of intercropped tropical perennial grasses on the production of sorghum-based silage - Costa, Nídia Raquel [UNESP]; Andreotti, Marcelo [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Pariz, Cristiano Magalhães [UNESP]; Lopes, Keny Samejima Mascarenhas [UNESP]; Leonardo De Almeida Yokobatake, Kazuo; Ferreira, João Paulo [UNESP]; Da Rocha Lima, César Gustavo [UNESP]; De Souza, Daniel Martins [UNESP] (Wiley, 2016)
Sorghum [Sorghum bicolor (L.) Moench] intercropped with tropical grasses can be used in silage production systems to increase the dry matter yield per area, provide pasture after sorghum harvesting and improve land-use efficiency (LUE). Our objective was to compare the production and quality of sorghum silage intercropped with palisade grass [Urochloa brizantha (A. Rich.) Stapf ‘Marandu’] or guinea grass [Megathyrsus maximus (Jacq.) B.K. Simon & S.W.L. Jacobs ‘Tanzânia’] with that of monocropped sorghum, the pasture in the off-season, as well as the land equivalent ratios of these systems during two growing seasons (2010–2011 and 2011–2012). The experiment was designed as a randomized complete block with four replicates. The treatments were: monocropped sorghum silage, sorghum silage intercropped with palisade grass and sorghum silage intercropped with guinea grass. The productivity of the intercropped systems was as high as that of the monocropped sorghum. The development of the sorghum was not affected by intercropping with grasses. Intercropping sorghum with tropical grasses generally increases the fiber content of the silage compared with monocropped sorghum; however, this is a viable option for producing feed with adequate nutritional quality. Intercropping sorghum with palisade grass improved the land equivalent ratio, resulting in greater LUE. Intercropping sorghum with palisade and guinea grass also improved the relative N yield compared with monocropped sorghum and did not influence aggressivity and relative crowding coefficient. The main benefit of these intercropping systems is established grazing during the off-season, which can be considered a good cultivation strategy for tropical regions.